Chemical Modification for the "Off‐/On" Regulation of Enzyme Activity. Issue 18 (26th May 2022) - Yu, Huaibin; Feng, Jiayi; Zhong, Fangrui; Wu, Yuzhou
Abstract: Enzymes with excellent catalytic performance play important roles in living organisms. Advances in strategies for enzyme chemical modification have enabled powerful strategies for exploring and manipulating enzyme functions and activities. Based on the development of chemical enzyme modifications, incorporating external stimuli‐responsive features—for example, responsivity to light, voltage, magnetic force, pH, temperature, redox activity, and small molecules—into a target enzyme to turn "on" and "off" its activity has attracted much attention. The ability to precisely control enzyme activity using different approaches will greatly expand the chemical biology toolbox for clarification and detection of signal transduction and in vivo enzyme function and significantly promote enzyme‐based disease therapy. This review summarizes the methods available for chemical enzyme modification mainly for the off‐/on control of enzyme activity and particularly highlights the recent progress regarding the applications of this strategy. Abstract : The methods for chemical enzyme modification are briefly summarized, mainly in enzyme activity regulation by incorporating external stimuli‐responsive featuresto turn its activity off and on. To precisely control enzyme activity using different approaches would greatly expand the chemical biology toolbox for clarification and detection of signal transduction and achieve precision disease therapy.